An Analysis of Code Mixing Used By Maestro Gate 107,5 Fm Radio Announcers In Muslim University of Indonesia - Rusdiah Salam; Ratnawati Ratnawati; Faradiba Amalia (Fakultas Sastra - Universitas Muslim Indonesia, 2016)
In this study, the writer explained about the analysis of the topic of Code Mixing occurs, the reasons, and also the frequency of Code Mixing happened among the radio announcers in Maestro Gate FM Radio of Moslem University of Indonesia. The writer uses descriptive qualitative method for analyze the use of Code mixing among the radio announcers; there are some tables and descriptive explanation of each table. When a word or a phrase from another language then Code Mixing occurred. This phenomenon happened to the radio announcers commonly. Especially the announcers of Maestro Gate FM Radio always mix the codes in some particular programs. The writer expected that the use of Code Mixing among the radio announcers that they should understand “why” and “how” Code-mixing happens in their life for communicating. So they can inform and share the main purpose of announcing some programs and give a lot of benefit through the languages they used. Because it can stimulate the environment to develop the other languages to be learned by the listener.